Progress benchmarking and test system to manage competitive fitness in Para sports - Baryaev, A.A.; Abalyan, A.G.; Fomichenko, T.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and scientifically substantiate a new progress benchmarking and test system for Para sports. Methods and structure of the study. The progress benchmark systems should be designed to facilitate competitive progress by the training goals set versus the sport-specific competitive performances of the best Paralympians with account of the sport functionality classifications (mentally retarded sports, blind sports, musculoskeletal disability sports, etc.). The study analyzes benefits of a new progress benchmarking and test system to manage competitive fitness in Para sports, customizable for every Para sport discipline and sports functionality (nosological) class. Results and conclusion. The new progress benchmark and test system was tested in application to Paralympic judo, athletics and sledge hockey. The test data and analysis have been proved beneficial for the progress benchmarking, training system management and competitive success. The Para sports competitive fitness and training system benchmarking database and practical training and competitive performances and progresses profiling data demonstrated benefits of the progress benchmarks and tests for the training system individualization purposes with due sensitivity to specific sport functionality classes and progress needs.